Management culture: the role of university startups - Novak, Larysa; Musiichuk, O.; Zuenko, N. (My University, 2020)
The authors found that the formation of a new management culture in higher education was initiated in the United States at the beginning of the 21st century. Two key recommendations from Congress on education policy have opened up a new source of income for universities. Universities were involved in the economic development strategy of the state. They turned from educational institutions into generators of a new management culture, which transformed the intellectual potential of young people into economic growth of the state and resulted in an increase in the wellbeing of society. The work discusses the peculiarities of the implementation of a new management culture in higher education in Ukraine. Three problems were identified and investigated that make it impossible to fully implement a new management culture in Ukrainian universities at this stage of state development.
Keywords: management culture; культура управління; university startups; університетські стартапи; US higher education; вища освіта США; university graduates; випускники університету; higher education in Ukraine; вища освіта в Україні; кафедра іноземних мов професійного спрямування